2018
DOI: 10.1126/sciadv.aao6250
|View full text |Cite
|
Sign up to set email alerts
|

Using para hydrogen to hyperpolarize amines, amides, carboxylic acids, alcohols, phosphates, and carbonates

Abstract: Parahydrogen is used to give efficient NMR detection of array of amines, amides, alcohols, carboxylates, carbonates, and phosphates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
173
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 127 publications
(189 citation statements)
references
References 41 publications
9
173
0
7
Order By: Relevance
“…The results are consistent with weak acetate binding to the IrIMes catalyst (fast on the 13 C NMR time scale). 13 C enhancements of up to 108‐fold were observed, which may be compared to recent results of ≈48‐fold and ≈140‐fold achieved in acetate via SABRE‐RELAY and spin‐relay within a cleavable agent, respectively (both at 9.4 T). We anticipate much larger enhancements should be possible by optimizing the experimental conditions of the present approach, particularly with respect to improving the magnetic shield and carefully avoiding relaxation sinks.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The results are consistent with weak acetate binding to the IrIMes catalyst (fast on the 13 C NMR time scale). 13 C enhancements of up to 108‐fold were observed, which may be compared to recent results of ≈48‐fold and ≈140‐fold achieved in acetate via SABRE‐RELAY and spin‐relay within a cleavable agent, respectively (both at 9.4 T). We anticipate much larger enhancements should be possible by optimizing the experimental conditions of the present approach, particularly with respect to improving the magnetic shield and carefully avoiding relaxation sinks.…”
Section: Resultssupporting
confidence: 61%
“…In summary, it is shown that “direct” hyperpolarization of 13 C spins of 1‐ 13 C‐acetate can be rapidly achieved using SABRE‐SHEATH, without the need for polarization to be relayed via either an exchangeable proton or a spin network within a cleavable substrate . The results are consistent with weak acetate binding to the IrIMes catalyst (fast on the 13 C NMR time scale).…”
Section: Resultsmentioning
confidence: 53%
“…The corresponding decay curve (Figure g) gives a T 1 value of ≈14±9 s at 0.3 T for the combined 13 C signal. This 13 C enhancement may be compared to that reported very recently by Iali et al., (≈48‐fold at 9.4 T), who demonstrated an alternate strategy for hyperpolarizing carboxylic acids by hyperpolarizing the exchangeable 1 H of NH 3 that hydrogen‐exchanges with the substrate in CD 2 Cl 2 . The value calculated here for imidazole 15 N enhancement includes the fact that magnetization achieved on one substrate 15 N spin becomes effectively “diluted” by a factor of two (because the two 15 N spins are magnetically equivalent).…”
Section: Methodssupporting
confidence: 58%
“…[75] This method begins by using SABRE to hyperpolarize an amine or ammonia, and proton exchanges allow the relay of polarization into the target substrate (Scheme 2). [75] This method begins by using SABRE to hyperpolarize an amine or ammonia, and proton exchanges allow the relay of polarization into the target substrate (Scheme 2).…”
Section: Discussionmentioning
confidence: 99%